2021
DOI: 10.4178/epih.e2021033
|View full text |Cite
|
Sign up to set email alerts
|

Health inequalities of 57,541 prisoners in Korea: a comparison with the general population

Abstract: OBJECTIVES: This study aimed to examine health disparities between prisoners and the general population in Korea.METHODS: We sought to estimate the prevalence of 17 physical and mental diseases using the nationwide medication prescription dataset among the total population of prisoners (n=57,541) in Korea. Age- and sex- standardized prevalence ratios (SPRs) were estimated to compare the disease prevalence between the prisoners and the general population. The disease prevalence for the general population was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…TB in incarcerated population has been a public health issue, globally ( 35 ). In a previous study comparing the prevalence of several diseases among prisoners and that among general population in South Korea, standardized prevalence ratio of pulmonary TB was 9.58, which demonstrated that prisoners were vulnerable population ( 36 ). In previous studies investigating LTBI status in incarcerated population, 10 out of 1,422 prisoners had concurrent active TB diseases in Brazil ( 37 ), and 2 out of 1,208 in Iran ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TB in incarcerated population has been a public health issue, globally ( 35 ). In a previous study comparing the prevalence of several diseases among prisoners and that among general population in South Korea, standardized prevalence ratio of pulmonary TB was 9.58, which demonstrated that prisoners were vulnerable population ( 36 ). In previous studies investigating LTBI status in incarcerated population, 10 out of 1,422 prisoners had concurrent active TB diseases in Brazil ( 37 ), and 2 out of 1,208 in Iran ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, 134 participants in Group C (11.5 per 1,000 participants) with previous TB history were excluded in this analysis, which was a higher proportion than that in Group A (1,956 participants, 4.4 per 1,000 participants) and Group B (110 participants, 0.4 per 1,000 participants). In addition, as we defined prevalent TB case as that notified within 30 days from the date of LTBI examination ( 12 ), we speculate that 30 days would be insufficient for diagnosis of TB in current setting of correctional facilities, as prisoner's access to healthcare services is limited and the diagnosis is often delayed ( 36 ). Therefore, incidence of TB in correctional facilities by LTBI status of each prisoner should be investigated, which would demonstrate the TB burden in correctional facilities better.…”
Section: Discussionmentioning
confidence: 99%
“…Lower educational level was de ned as fewer than 9 years of education (middle school), and non-married status included individuals unmarried, separated, divorced, or widowed. Unemployment and low income status were also included, and individuals with low income were de ned as those receiving National Medical Aid services [19]. The Korean National Health Insurance system ensures coverage for all national populations, and National Medical Aid services are provided based on the National Basic Living Security Act to those who struggle to maintain an adequate standard of living.…”
Section: Sociodemographic Variablesmentioning
confidence: 99%
“…Health inequalities are unequal and disadvantageous differences in the health of different populations, such as life expectancy or access to healthcare, which are socially determined 3. PEI have a high prevalence of physical and psychiatric morbidity, with many coming from marginalised backgrounds, experiencing homelessness or with limited educational backgrounds 1 4–6. There are complex social problems, including being deprived of liberties, a lack of social and familial support and violence, each contributing to ill health 2 5…”
Section: Introductionmentioning
confidence: 99%